The Search for Radiation Standards and Science Diplomacy in the Interwar Period - Nielsen, Aske Hennelund; Rentetzi, Maria (Physics in Perspective, 2024)
This paper argues that international cooperation on devising radiation standards and measuring devices has been an issue not only of national concern but of binational and international conflict in the interwar period. Moreover, the production of radiation safety standards and radiation units gradually became a diplomatic process that underlined national rivalries and depended on political and diplomatic interests. As a result of this diplomatic process, early major scientific actors on radiation research lost prominence. The need to decide on radiation standards that could address medical, military and industrial concerns was therefore acute long before the 1950s and the establishment of international organizations such as the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) and the International Atomic Energy Agency (IAEA), that took the lead in regulating the uses of ionizing radiation in the postwar perio
Keywords: International Radiological Congress; Inter-war period; Science diplomacy; Scientific standards; Radiation protection; Radiology